2015
DOI: 10.1186/s12885-015-1989-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 20 positive circulating tumor cells are a marker for response after neoadjuvant chemoradiation but not for prognosis in patients with rectal cancer

Abstract: BackgroundSeveral studies have shown, that circulating tumor cells (CTC) have a negative prognostic value in colorectal cancer patients. Aim of this study was to evaluate the role of CTC in specifically rectal cancer patients regarding the influence on overall survival and to elucidate the impact of CTC in predicting response after chemoradiation (RCTX).MethodsIn this prospective monocentric study 267 patients with rectal cancer were included. Patients with locally advanced tumors were treated with RCTX follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
6
29
0
Order By: Relevance
“…We included in our study exclusively patients with colon cancer as we have previously reported that in rectal cancer DTC and CTC have no prognostic influence on OS [12]. In accordance to our findings several other groups have also described that in rectal cancer CTC are not a prognostic factor for OS [3032].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We included in our study exclusively patients with colon cancer as we have previously reported that in rectal cancer DTC and CTC have no prognostic influence on OS [12]. In accordance to our findings several other groups have also described that in rectal cancer CTC are not a prognostic factor for OS [3032].…”
Section: Discussionsupporting
confidence: 80%
“…We have previously shown that in rectal cancer patients CTC detection by CK20 expression is not a prognostic marker, but a marker for response to neoadjuvant chemoradiation [12]. This finding even more stresses the biological differences and distinct modes of metastasis of colon and rectal cancer, which is underestimated in most clinical trials.…”
Section: Introductionmentioning
confidence: 96%
“…CTCs were decreased in blood samples collected after nCRT from responders while no significant change was observed in non-responders [121]. Two studies assessed mRNA expression of cytokeratin-20 ( CK20) in blood mononuclear cells [122] and CEA/CK20/CD133 in peripheral blood [123] using RT-PCR to identify CTCs in rectal cancer. Although PCR-based CTC detection does not directly observe and enumerate CTCs and therefore might be less specific compared to immunocytologic methods [117], detection rates of these markers were significantly associated with nCRT response [122] and local recurrence [123].…”
Section: Biomarkers In Bloodmentioning
confidence: 99%
“…Currently, there is limited evidence showing that CTCs detection at baseline can predict the response to systemic therapy in GI cancers (60,61,83,85,87,88,90,91,(95)(96)(97)(98). However, a few studies have demonstrated the predictive value of CTCs detection during chemotherapy (summarized in Table 2).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%